Modelling flow and pressure controlled pump stations with application to optimal pump scheduling - Elhay, Sylvan; Fischer, Michael; Piller, Olivier; Deuerlein, Jochen; Simpson, Angus Ross (Cambridge Prisms: Water, 2025)
Many pressurized water distribution systems use pumps for the transport of water and tank filling. Modelling groups of parallel pumps with a common control target remains an open problem in hydraulic modelling. In this article, the authors show how to model flow- and pressure-controlled pumping stations in the analysis of hydraulic pipe networks. The process comprises two distinct phases. In the first phase, the pump station is regarded as a single surrogate link connected to the remainder of the network. The flow and head gain at the active pump stations are computed to ensure satisfaction of the network load requirements. In the second phase, an energy minimization problem is formulated for each local pump station to ascertain the optimal pump speed and which pumps should be active. For real-time applications, very significant improvements are possible by hybrid modelling, such as coupling deterministic modelling, surrogate modelling and neural networks. This can lead to performance improvement with a magnitude of the order of $ {10}^5 $ . The application to optimal pump scheduling in the context of strongly varying electricity tariffs is summarized.